HUBUNGAN KUALITAS PELAYANAN KEPERAWATAN TERHADAP KEPUASAN PASIEN LANSIA DI POSYANDU LANSIA DESA BUMI PRATAMA MANDIRA - R.A Fadila; Widiyawati, Nanik (Jurnal Kesehatan dan Pembangunan, 2025)
Community satisfaction as service recipients is a comparison between the services received and the expected services. Service quality is very important because with good service, patient satisfaction will also have a positive impact on the elderly posyandu. The aim of this research is to determine the relationship between the quality of nursing services and the satisfaction of elderly patients at the Posyandu for the Elderly in Bumi Pratama Mandira Village. Method: the research used in this research is an explanatory research study. The population in this study was all elderly people at the Posyandu for the Elderly in Bumi Pratama Mandira Village, totaling 50 respondents. The sampling technique used total sampling with a sample of 50 respondents. Data collection uses a questionnaire. Data analysis used univariate and bivariate analysis with the chi square test. The results of the univariate analysis showed that out of 50 respondents, 31 respondents (62%) were satisfied and 19 respondents were less satisfied (38%), 41 respondents (82%) had good service quality and 9 respondents had poor service quality. (18%). The results of the chi square statistical test showed that there was a relationship between the quality of nursing services and the satisfaction of elderly patients at the Posyandu for the Elderly in Bumi Pratama Mandira Village (p value = 0.018 < ? 0.05). Suggestion: it is hoped that nurses and officers at the Bumi Pratama Mandira Village Elderly Posyandu will try to improve the services provided by providing support or motivation to work well in order to meet patient expectations so as to increase the satisfaction of elderly people who visit the posyandu.